Use of debt covenants in small firms - Chenchuramaiah T. Bathala; Oswald D. Bowlin; William P. Dukes (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
This paper examines the structure of debt covenants in small firms, with emphasis on privately owned firms. It is based on a survey of a large sample of firms drawn from the S&P Register of Corporations. The findings show that debt covenants imposed on small firms differ according to the firm type (privately owned or publicly owned), debt level, the borrowing cost, and the source of financing (bank or other sources). The evidence is generally consistent with the arguments relating to stockholder-bondholder agency cost conflicts and the Costly Contracting Hypothesis of Smith and Warner (1979).
Keywords: 650